Knowledge and treatment seeking behavior regarding malaria among the residents of tribal dominated areas of Mandla district in central India – A cross-sectional study - Kunal Peepre; Tomar, Shashi Prabha; Thakur, Aditya; Kasar, Pradeep Kumar (Asian Journal of Medical Sciences, 2023)
Background: Malaria is both a result and a cause of a lack of development. Dearth of information, education, and communication activities and awareness, knowledge regarding malaria is poor particularly in tribal population of Mandla. Aims and Objectives: The aim of the study was to assess the malaria knowledge and treatment-seeking behavior among the residents of the tribal dominated areas of Mandla district and to study their association with the sociodemographic characteristics. Materials and Methods: A total of eight villages were selected from which 25 households were randomly selected making a total sample size of 200 households, from these 200 households, 200 adult respondents were identified for administration of the study questionnaire. Results: The age of the respondents ranged from 18 to 80 years, with a mean age of 37 years (SD=14.7). Overall, 48.5% of respondents had correct knowledge about perceived cause of getting malaria. The treatment seeking behavior of the respondents were associated with sociodemographic profile of the participants the age of the participants, the association was found to be highly statistically significant (P=0.001). Conclusion: Malaria prevention campaigns should be tailored according to knowledge gaps, practices, environment, resources, and preferences in different areas of the Mandla District, using the health education/awareness most likely to outreach the far corners of the district where most residents were tribals.